Variation in the hydrological cycle in the Three-River Headwaters Region based on multi-source data - Yang, Yong; Chen, Rensheng; Ding, Yongjian; Zhao, Qiudong; Li, Hongyuan; Liu, Zhangwen (Frontiers in Environmental Science, 2022)
The hydrological processes in the Three-River Headwaters Region (TRHR), which is located in the Qinghai-Tibetan Plateau and includes the Yangtze River Headwater Region (YARHR), the Yellow River Headwater Region (YERHR), and the Lantsang River Headwater Region (LARHR), have changed under climate warming. Based on multi-source data, the spatial and temporal changes in precipitation, evapotranspiration, soil water storage, glacier melt, snowmelt and runoff in the TRHR from 1982 to 2014 were comprehensively analysed. The annual precipitation data for the TRHR from ERA5-Land, the Climatic Research Unit, the China Meteorological Forcing Dataset and the Global Land Data Assimilation System (GLDAS) all showed an increasing trend; the annual evapotranspiration data from ERA5-Land, GLDAS, Global Land Evaporation Amsterdam Model (GLEAM) and Terrestrial Evapotranspiration Dataset across China (TEDC) all showed an increasing trend; and the annual soil water storage data from ERA5-Land, GLDAS and GLEAM all showed an increasing trend. The annual snowmelt data from ERA5-Land, GLDAS and SMT-Y datasets all showed a decreasing trend. The annual glacier melt increased in the YARHR and YERHR and decreased in the LARHR. The increases in precipitation, evapotranspiration, soil water content and glacial melt, and the decreases in snowfall and snowmelt indicate an accelerated hydrological cycle in the TRHR over the 1982 to 2014 period. The significant increase in precipitation is the main reason for the significant increase in runoff in the YARHR. The increase in precipitation in the YERHR was less than the sum of the increase in evapotranspiration and soil water storage, resulting in a decreasing trend of runoff in the YERHR. The increase in precipitation in the LARHR was slightly larger than the sum of that in evapotranspiration and soil water storage, and there was an insignificant increase in the runoff in the LARHR.